Representation in activation the interlocution of interior spaces - Ahmed Louay Al Bajjari; Harith Assad Abdulrazzaq (Iraqi Journal of Architecture and Planning, 2018)
The subject of representation in the Interior Design & Interior Architecture occupied an important place& a wide range of interesting by theorists, critics & practitioners of the jurisdiction of interior design, andcame this interest in narrative theory & practical both in terms of the fact that the products of interior designare language & communication system with the receiver, This has pour practitioners jurisdiction interest togenerate meanings intended and delivered through a formula of representation, while a theorists & critics madea lot of explanations in an attempt to discover the meaning of the work or approach, achieving basis formula ofrepresentation for dialogic language through the formation of form in the interior space.In order to highlight the required framework, research made use of literary and architectural studies tocome out with a detailed theoretical framework for the Representation in interior design. This included manytopics : What is meant by, Representation, what is the shift from formal references, How to deal withreferences , the new generated meanings, interlocution of language in design.The realization of this framework represented the first stage of the method followed in this study. As forthe requirements of the second stage (the application of the theoretical framework), which were delimited bythe choice of two groups of projects representing the most prominent architects of the Post-Modernismapproaches & Deconstruction school, as also requests the application for the research procedure to identifyindicators of the theoretical framework of controlled application, research objectives, method of collectinginformation, measurement of variables and method of measurements on projects in the practical study &analyzed there results.A discussion of the conclusions of this study within many perspectives was held; the first of whichemphasized the importance of the theoretical framework set forth concerning the concept of the Representationas an interlocution of language through the well-established theoretical knowledge presented in the Post-Modernism approaches & Deconstruction school.